2023
DOI: 10.1590/1414-462x202331020104
|View full text |Cite
|
Sign up to set email alerts
|

Estudo descritivo de casos notificados de febre maculosa em São Paulo, Rio de Janeiro e Minas Gerais entre 2007 e 2016

Abstract: Resumo Introdução A febre maculosa é uma doença infecciosa aguda causada por bactérias do gênero Rickettsia e transmitida por carrapatos que pode levar à hospitalização e, eventualmente, a óbito por causa de quadros mais graves. Objetivo O objetivo deste artigo foi descrever o cenário epidemiológico da doença nas três unidades federativas de maior número de notificações e óbitos pela doença no Brasil entre 2007 e 2016. Método Estudo epidemiológico descritivo com base nos dados das fichas de investigação par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…A study carried out from 2014 to 2019 in Mexico with 129 patients who died due to Rocky Mountain Spotted Fever (RMSF) did not identify a difference between genders, diverging from the research, which identified a higher proportion of deaths in males [11]. In Brazil, other studies that evaluated the epidemi- ological profile of RMSF identified a higher incidence of involvement in males [12]. This data may be related to the greater contact of this public with the vector, as work activities in peri-urban and rural regions are predominantly occupied by male workers, a reason corroborated by a study carried out in the United…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A study carried out from 2014 to 2019 in Mexico with 129 patients who died due to Rocky Mountain Spotted Fever (RMSF) did not identify a difference between genders, diverging from the research, which identified a higher proportion of deaths in males [11]. In Brazil, other studies that evaluated the epidemi- ological profile of RMSF identified a higher incidence of involvement in males [12]. This data may be related to the greater contact of this public with the vector, as work activities in peri-urban and rural regions are predominantly occupied by male workers, a reason corroborated by a study carried out in the United…”
Section: Discussionmentioning
confidence: 91%
“…Regarding the environments of contamination, it is worth highlighting the urbanization of the BSF, which can be explained by the proximity of residences to forest areas due to the disorderly growth of urban areas, directly affecting the natural habitat of wild animals and increasing the risk of contact with ticks [12].…”
Section: Discussionmentioning
confidence: 99%
“…According to the Epidemiological Bulletin of the Ministry of Health [8], between 2007 and 2021, 36,497 cases of Spotted Fever were reported in Brazil, of which 2545 cases were confirmed. However, most cases are underreported [9]. Most of the BSF records occur in urban areas, with the Southeast region having the highest incidence rate of cases, due to the presence of A. sculptum and amplifying hosts [10,11].…”
Section: Introductionmentioning
confidence: 99%